2004
DOI: 10.1023/b:viru.0000032786.45323.6b
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Major Early-Transcribed Gene of Trichoplusia ni Single Nucleocapsid Nucleopolyhedrovirus Using the Baculovirus Expression System

Abstract: An early transcribed gene (me-53) of a South Africa strain of Trichoplusia ni single nucleocapsid nucleopolyhedrovirus (TnSNPV) was sequenced and identified. It has an open reading frame of 1146 nucleotides that encodes a protein of 382 amino acids with a molecular mass of 45.2 kDa. The deduced protein sequence alignment of 13 baculovirus ME-53s indicated that the TnSNPV ME-53 shares the highest homologies with NPV subgroup II-A Spodoptera exigua multiple and Mamestra configurata (Maco) nucleopolyhedrovirus ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Pr70 (BV/ODV-C42) has been proven to mediate the nuclear entry of P78/83. , As a conserved ODV envelope protein, ODV-E18 has been shown to mediate budded virus production, whereas ODV-E28 has been characterized as a structural ODV-associated envelope protein . LEF3 also participates in DNA replication and (or) the very late expression of genes. ,, PEP1 and PEP2 are a type of polyhedrin envelope proteins that are located on the surface of OBs and play an important role in polyhedrin formation. , ME-53 is an early expression protein with zinc finger-like motifs at its C-terminus . An me53 knockout could block viral DNA replication, nucleocapsid formation, and consequently BV and ODV production .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pr70 (BV/ODV-C42) has been proven to mediate the nuclear entry of P78/83. , As a conserved ODV envelope protein, ODV-E18 has been shown to mediate budded virus production, whereas ODV-E28 has been characterized as a structural ODV-associated envelope protein . LEF3 also participates in DNA replication and (or) the very late expression of genes. ,, PEP1 and PEP2 are a type of polyhedrin envelope proteins that are located on the surface of OBs and play an important role in polyhedrin formation. , ME-53 is an early expression protein with zinc finger-like motifs at its C-terminus . An me53 knockout could block viral DNA replication, nucleocapsid formation, and consequently BV and ODV production .…”
Section: Resultsmentioning
confidence: 99%
“…15,22 ME-53 is an early expression protein with zinc finger-like motifs at its C-terminus. 71 An me53 knockout could block viral DNA replication, nucleocapsid formation, and consequently BV and ODV production. 80 However, new data suggest that ME-53 does not affect DNA replication but is required for efficient BV production.…”
Section: Comparison Of Odv Proteins Identified In This Study and Prot...mentioning
confidence: 99%
“…With the early and late specific motifs in the putative promoter regions, me53 gene was reported to transcribe at the early and late phases of viral infection [21]. It is unclear what is the relationship between DNA replication and late gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al (33) revealed that me53 from Trichoplusia ni single nucleocapsid nucleopolyhedrosis virus could be successfully expressed from its native promoters in a recombinant AcMNPV in the Sf9 and BTI-Tn-5b1 (Hi5) insect cell lines. Their study confirmed the transcriptional profile of AcMNPV me53 and indicated that the T. ni single nucleocapsid nucleopolyhedrosis virus me53 was similarly transcribed from unique sites at both early and late times p.i.…”
mentioning
confidence: 99%